Hidden Culture in Different Conceptual Meaning of Indonesian Popular Food among Javanese People in Java Island - Irma Nirmala (ETNOLINGUAL, 2017)
Abstract Different conceptual meaning of Indonesian popular food can be happened among Javanese people in Java Island due to having distinctive food perception. When people in East Java order the popular food (Bakso or Tempe tepung) at food stall, café, or restaurant in Central Java, they will probably get food which is not same as their perception or experience like in East Java. It is caused people in Central Java have own conceptual meaning of food in spite of having same name. This study finds two possibilities of conceptual meaning. They are having same name but different conceptual meaning and vice versa. Obviously its conceptual meaning represents their culture, such as the taste of food, the use of food in special event, type of food, and the eaters. Even though the meal itself has become a part of culture, because it is belong to outcome from the local community. It has gone that way, because people in group of community or area repeat cooking activity many times. It becomes habit; and it is continued by next generation.